Methods of resolving criminal dispute without a trial: Options for an accused - Ab Aziz, Norjihan; Mohamad Amin, Noorshuhadawati; Ab Hamid, Zuraini (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
In the Malaysian criminal justice system, upon a charge is read to an accused, he may claim a trial, or plead guilty at an early stage of a criminal proceeding or applies for plea bargaining. A trial is not necessary if the accused plead guilty or applies for plea bargaining. It is undeniable that regardless of a criminal case is resolved through trial, or without trial, if the accused is found guilty of an offence and convicted, he will be punished accordingly. However, a sentence is lighter if the accused pleads guilty or applies for plea bargaining at an early stage of a criminal proceeding than convicted after the full trial. Meanwhile, under the auspice of restorative justice, a criminal case can also be resolved by way of victim-offender mediation, family group conferencing, and sentencing circle depend on the nature of a criminal case and the parties. The United Nation and the European Union recognise and encourage state members to adopt restorative justice as part of the criminal justice system. While other countries such as New Zealand, Sweden and the United Kingdom have legalised the restorative justice process and implemented it in the criminal justice system, Malaysia still silences on this. Definitely there are advantages in the restorative justice since it is accepted internationally and practiced in some countries. Therefore, this paper aims to examine resolution of a criminal case without a trial in Malaysia and identify its weaknesses if any. It also aims of this paper to analyse the restorative justice processes, and its implementation in other countries. It is recommended that Malaysia shall recognise other modes of criminal dispute resolution so that the accused can have more options to settle the criminal case without a trial which can meet his need and interest. The research utilises the doctrinal legal research based on analysis of primary and secondary sources such as statutes, case law, books, and journal articles.